2000
DOI: 10.1016/s0735-1097(00)00672-0
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of coronary artery stenosis using contrast-enhanced three-dimensional breath-hold magnetic resonance coronary angiography

Abstract: Oblique projection contrast-enhanced MR coronary angiograms obtained within one single breath-hold permit identification of patients with coronary stenoses in the proximal and mid segments of the major coronary arteries with satisfactory accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 35 publications
4
47
1
4
Order By: Relevance
“…30 Three major groups or "generations" of coronary MRA techniques can be discerned. From all techniques available, 2D breathhold CMRA scans, 31 3D retrospective respiratory navigator-gated coronary MRA, [32][33][34][35][36][37][38][39] and breathhold 3D CMRA 40,41 have been evaluated clinically (Table 2 and Figure 5).…”
Section: Mr Coronary Angiographymentioning
confidence: 99%
“…30 Three major groups or "generations" of coronary MRA techniques can be discerned. From all techniques available, 2D breathhold CMRA scans, 31 3D retrospective respiratory navigator-gated coronary MRA, [32][33][34][35][36][37][38][39] and breathhold 3D CMRA 40,41 have been evaluated clinically (Table 2 and Figure 5).…”
Section: Mr Coronary Angiographymentioning
confidence: 99%
“…MIP images generated from the 2D spiral stack consistently detected stenoses and also delineated vessel wall irregularities, while only three (reader 1) and two (reader 2) of four normal vessels were classified correctly. Similarly, a rather low specificity of 57% (sensitivity, 94%) was reported for the combination of an extravascular Gd-based CM with a 3D breath-hold approach of comparable resolution (16).…”
Section: Discussionmentioning
confidence: 92%
“…Two recent studies in patients demonstrated the feasibility of a 3D breath-hold approach when combined with the conventional extravascular Gd-DTPA, although pre-and postcontrast SNR and CNR were not compared in these two studies (16,25). The use of an intravascular CM would clearly be beneficial in combination with a breath-hold approach by offering the possibility to repeatedly image the various segments of the coronary arteries until diagnosis is established.…”
Section: Discussionmentioning
confidence: 99%
“…van Geuns et al [7] assessed the diagnostic accuracy of this approach and reported that 69% of segments were assessable, with sensitivity and specificity of 92% and 68%, respectively, for the detection of >50% luminal stenosis. One advantage of the breath-hold technique is that it allows for imaging of coronary arteries during the first pass of extracellular MR contrast media (e.g., Gd-DTPA), which rapidly diffuses from the intravascular space to the interstitial space after intravenous administration [8][9][10][11]. Regenfus et al [11] obtained breath-hold 3D coronary MRA immediately after injecting extracellular MR contrast agent at a flow rate of 1 ml/s and reported 94% sensitivity and 57% specificity for detecting significant CAD.…”
Section: Introduction Coronary Mra; Achilles Heel Of Cardiac Mri?mentioning
confidence: 99%
“…One advantage of the breath-hold technique is that it allows for imaging of coronary arteries during the first pass of extracellular MR contrast media (e.g., Gd-DTPA), which rapidly diffuses from the intravascular space to the interstitial space after intravenous administration [8][9][10][11]. Regenfus et al [11] obtained breath-hold 3D coronary MRA immediately after injecting extracellular MR contrast agent at a flow rate of 1 ml/s and reported 94% sensitivity and 57% specificity for detecting significant CAD. However, the short imaging time of the breath-hold technique is a tradeoff with reduced spatial resolution and 3D volume coverage.…”
Section: Introduction Coronary Mra; Achilles Heel Of Cardiac Mri?mentioning
confidence: 99%